PERANCANGAN JARINGAN FIBER TO THE HOME (FTTH) BERTEKNOLOGI GIGABIT PASSIVE OPTICAL NETWORK (GPON) DI PERUMAHAN CITRALAND PALU - Toago, Sembara P.; Alamsyah, Alamsyah; Amir, Ardi (MEKTRIK)
Abstract This research is aimed at how to design network system fiber to the home with the technology of GPON, analize fiber to the home with GPON technology implements, evaluate the use of technology as GPON access device in channeling triple play service, and make the planning design of fiber to the home. This research was conducted in residential Citraland Palu at Trans Sulawesi Tondo. From the results of this research obtained link power budget calculation, including loss fiber = 3.8815 dB, loss connected = 0.6 dB, loss connector = 0.8 dB, the recive signal power = 8,95 x 10-6 Watt, dan S/N = 1.157 x 10-10 A. While for the calculation of damping in every housing average by 22.9901 dB, while the lowest damping is 22.7874 dB, and the higest is 23.0566 dB. While in the planning design of these network is needed 1 GPON OLT, 1 device, 1 piece of ODC Passive Spiltter dengan with configuration 1:4 on the ODC, 61 piece Passive Spiltter with configuration 1:8 on the ODP, 61 ODP’s devices with 12 port in every device 480 devices of ONU. Keywords: FTTH (Fiber To The Home), GPON, Fiber Optic, Passive splitter.